2016
DOI: 10.1002/jcb.25570
|View full text |Cite
|
Sign up to set email alerts
|

Influence of 6‐Hydroxydopamine Toxicity on α‐Synuclein Phosphorylation, Resting Vesicle Expression, and Vesicular Dopamine Release

Abstract: Post mortem studies on familial and sporadic Parkinson's disease patient striatal tissue have shown that nearly 90% of α-synuclein deposited in Lewy-bodies is phosphorylated at serine-129 (pSyn-129) as opposed to only 4% in normal human brain. We aimed to find the influence of endogenous neurotoxin 6-hydroxydopamine (6-OHDA) on α-synuclein phosphorylation, resting vesicles, and vesicular dopamine release. The relative distribution of pSyn-129+ cells in apoptotic and non-apoptotic populations at different 6-OHD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 78 publications
(103 reference statements)
3
13
0
Order By: Relevance
“…Perfeito et al [118] showed through an in vitro model that exposure to ferrous iron and rotenone resulted in increase in pSyn. A similar increase was reported by Ganapathy et al [112] in the presence of the endogenous toxin 6-hydroxydopamine. Proteosomal inhibition by epoxomycin and increased oxidative stress by paraquat treatment has led to increases in pSyn [97].…”
Section: Oxidative Stress and α-Syn Phosphorylationsupporting
confidence: 88%
See 3 more Smart Citations
“…Perfeito et al [118] showed through an in vitro model that exposure to ferrous iron and rotenone resulted in increase in pSyn. A similar increase was reported by Ganapathy et al [112] in the presence of the endogenous toxin 6-hydroxydopamine. Proteosomal inhibition by epoxomycin and increased oxidative stress by paraquat treatment has led to increases in pSyn [97].…”
Section: Oxidative Stress and α-Syn Phosphorylationsupporting
confidence: 88%
“…In studies using PD rat models, the phospho-resistant S129A was found to be localized in the nucleus at higher levels than the S129D form, and was found to correlate with enhanced toxicity [110,111]. Our group too demonstrated the nuclear localization of pSyn in SH-SY5Y cells under 6-hydroxydopamine toxicity [112]. Gonçalves and Outeiro [113] showed that S129 phosphorylation modulates the shuttling of α-Syn between nucleus and cytoplasm in human neuroglioma cells, using photo-activatable green fluorescent protein as a reporter.…”
Section: Phosphorylation At Serine129 Modulates α-Synuclein Protein-pmentioning
confidence: 63%
See 2 more Smart Citations
“…Nevertheless, there is evidence that α-synuclein is involved in the lesions caused by 6-OHDA [ 67 ]. 6-OHDA increased, in a concentration-dependent manner, the content of monomeric and oligomeric α-synuclein in SH-SY5Y cells in vitro and enhanced the phosphorylation of α-synuclein (pSyn-129) characteristic for PD [ 68 ], which is considered to be an LB-like feature [ 65 ]. These properties of the 6-OHDA model are consistent with the changes in the brains of Sigmar1 knockout mice [ 23 ].…”
Section: Introductionmentioning
confidence: 99%